A New Species Of Issikiella From The Amazon Basin (Mecoptera: Bittacidae) - Penny, Norman D.; Arias, Jorge Ramon (Acta Amazonica, 1983)
A new species of Issikiella is described from southern Pará State, Brazil, and compared with the other two known species.